THE MEDIATING ROLE OF FINANCIAL INCLUSION IN THE RELATIONSHIP BETWEEN FINANCIAL LITERACY AND INDIVIDUALS BEHAVIOR OF SAVINGS AND BORROWING - AN EXPLORATORY STUDY FOR A SAMPLE OF IRAQI BANKS - Mustafa Hussein Hassan; Sadiq Hussein Abdul Hassan (Scholars Digest Publishing, 2023)
Aim of research tests the effect increasing the awareness of the members of society financially on their savings and borrowing behavior, and determines the role of financial inclusion that can be exercised by banks in enhancing this effect as an intermediary variable, so used questionnaire as a tool for data collection and distribute more 170 of which were accepted, and employment a number of statistical tools were used to analyze the answers of the research sample and test its hypotheses. Therefore, the researcher recommended the need for banks to intensively strengthen efforts to raise awareness of individuals and ensure their better access to the services they provide to ensure the promotion of positive behavior of the customer.
Keywords: financial inclusion, financial literacy, saving behavior, borrowing behaviour.